2006
DOI: 10.1055/s-2006-926793
|View full text |Cite
|
Sign up to set email alerts
|

Partielle k-Raum-Auslesung mit Null-Interpolation bei Phasenkontrast-Flussmessungen: In-vivo- und In-vitro-Validierung

Abstract: Partial k-space sampling can be used to reduce scan time without a significant decrease in the accuracy or precision of phase-contrast flow measurements in large arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In a study using ZIP to measure the flow velocity of the aorta, it has been reported that the accuracy and precision are maintained while shortening the imaging time by 2/3. 78 However, it was not a study of small blood vessels or high spatial resolution.…”
Section: Cerebral Blood Vesselsmentioning
confidence: 99%
“…In a study using ZIP to measure the flow velocity of the aorta, it has been reported that the accuracy and precision are maintained while shortening the imaging time by 2/3. 78 However, it was not a study of small blood vessels or high spatial resolution.…”
Section: Cerebral Blood Vesselsmentioning
confidence: 99%